Comparative transcriptome analysis identifies candidate genes related to sucrose accumulation in longan (Dimocarpus longan Lour.) pulp - Li, Yun; Ren, Rui; Pan, Ruoyun; Bao, Yuying; Xie, Tao; Zeng, Lihui; Fang, Ting (Frontiers in Plant Science, 2024)
Sucrose content is one of the important factors to determine longan fruit flavor quality. To gain deep insight of molecular mechanism on sucrose accumulation in longan, we conducted comparative transcriptomic analysis between low sucrose content longan cultivar ‘Qingkebaoyuan’ and high sucrose content cultivar ‘Songfengben’. A total of 12,350 unique differentially expressed genes (DEGs) were detected across various development stages and different varieties, including hexokinase (HK) and sucrose-phosphate synthase (SPS), which are intricately linked to soluble sugar accumulation and metabolism. Weighted gene co-expression network analysis (WGCNA) identified magenta module, including DlSPS gene, was significantly positively correlated with sucrose content. Furthermore, transient expression unveiled DlSPS gene play crucial role in sucrose accumulation. Moreover, 5 transcription factors (MYB, ERF, bHLH, C2H2, and NAC) were potentially involved in DlSPS regulation. Our findings provide clues for sucrose metabolism, and lay the foundation for longan breeding in the future.